Epidemiological Characteristics of the Human Papilloma Virus in Women in Uzbekistan - Jamila, Rakhmanova (International Journal of Psychosocial Rehabilitation, 2020)
This article examines the epidemiological characteristics of the human papillomavirus in Uzbekistan. The report presents data on the prevalence of phylogenetic groups identified as a result of the research carried out, as well as the age-specific features of the spread of the human papillomavirus and their combination. Recommendations on preventing the spread of human papillomavirus by introducing vaccination and conducting screening tests for women to prevent cervical cancer.